2019
DOI: 10.2196/preprints.13560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Web-Based Monitoring System for Power Tilt-in-Space Wheelchairs: Formative Evaluation (Preprint)

Abstract: BACKGROUND A power tilt-in-space wheelchair meets many clinical purposes, including pressure management, increased postural control, and pain management. However, there is a significant gap between the use of tilt as recommended by clinicians and its actual usage. A Web-based electronic health (eHealth) intervention, including a goal setting, monitoring, reminder, and feedback system of the use of power tilt-in-space wheelchairs was developed. The intervention incorporates behavior chan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To this end, we will use the 'think aloud' method [45], in which care providers and patients can speak aloud any words in their mind as they read through parts of the intervention plan. The think-aloud research method has been demonstrated to provide valid data on participant thinking and was successfully used in other intervention development studies [46,47]. Based on the results obtained, further modifications will be made, resulting in a pre-tested version of the intervention plan ready for implementation in practice.…”
Section: Step 4: Develop a Tailored 'Medical Dashboard' Based Intervementioning
confidence: 99%
“…To this end, we will use the 'think aloud' method [45], in which care providers and patients can speak aloud any words in their mind as they read through parts of the intervention plan. The think-aloud research method has been demonstrated to provide valid data on participant thinking and was successfully used in other intervention development studies [46,47]. Based on the results obtained, further modifications will be made, resulting in a pre-tested version of the intervention plan ready for implementation in practice.…”
Section: Step 4: Develop a Tailored 'Medical Dashboard' Based Intervementioning
confidence: 99%